Teratogenic hazard of BPEI-coated silver nanoparticles to Xenopus laevis. Issue 3 (16th March 2017) - Colombo, Anita; Saibene, Melissa; Moschini, Elisa; Bonfanti, Patrizia; Collini, Maddalena; Kasemets, Kaja; Mantecca, Paride
Abstract: Silver nanoparticles (AgNPs) are among the most exploited antimicrobial agents and are used in many consumer products. Size and surface reactivity are critical physico-chemical properties responsible for NPs toxicity, and surface coatings, often used to functionalize or stabilize AgNPs, can influence their toxic profile and biocompatibility. In the current study the developmental toxicity of (1) negatively charged citrate-coated AgNPs (Cit-AgNPs), (2) positively charged branched polyethylenimine-coated AgNPs (BPEI-AgNPs), and (3) Ag + (from 0.0625 to 0.75 mg Ag/L) was investigated by the standard Frog Embryo Teratogenesis Assay – Xenopus (FETAX). In order to identify the most sensitive developmental phase, embryos were also exposed during different embryonic stages. Morphological and bio-physical studies were performed to characterize tissue lesions and NP uptake. The results suggest that Ag + was strongly embryo-lethal. Contrary to Cit-AgNPs, the positively charged BPEI-AgNPs exert a concentration-dependent effect on lethality and malformations of embryos. The BPEI-AgNPs showed the highest teratogenic index (TI = 1.6), pointing out the role of functional coating in determining the developmental hazard. The highest susceptibility to BPEI-AgNPs was during early embryogenesis, when embryos are still enclosed in the fertilization envelope, and the post-stomodeum opening stages, when NPs ingestion occurs. In BPEI-AgNPs treated larvae, the histological examination revealed irregular intestinal diverticula coupled with edematous connective tissue. Small NPs aggregates are mapped throughout the intestinal mucosa and secondary target organs by two-photon excitation microscopy. We conclude that a teratogenic risk may be associated with BPEI-AgNPs exposure, but the modality of NP-tissue interactions and the teratogenic mechanism need further investigations to be better defined.